EFFECTIVENESS OF GROUP GUIDANCE USING SELF MANAGEMENT TECHNIQUES TO REDUCE ACADEMIC BURNOUT IN STUDENTS - Sipahutar, Siti Komariah; Arsini, Yenti (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2024)
Academic burnout is an increasingly significant phenomenon in the world of education, especially among students. In the educational context, academic burnout can have an impact on the quality of education and student learning outcomes. Sstudents who experience it academic burnout, which is characterized by difficulty concentrating, getting bored and tired easily, not being interested in the material being taught and often postponing work (school assignments), getting angry easily, not having confidence in one's abilities, feeling tired because of the large amount of school assignments. This research aims to determine the effectiveness of self-management techniques in reducing academic burnout among students at MAN 1 LABURA.  This research uses a quantitative pattern approach as an experimental design. The number of samples used in this research was 20 students from class XI MIPA 2 and Class XI IPS 2 with a population of 65 students from 2 classes. The sampling technique in this research uses a purposive sampling technique where sampling is carried out based on considerations according to certain criteria. The data collection technique in this research uses a questionnaire. The data analysis techniques used are descriptive statistics and tests independent samples test (t test) using the SPSS program version 26.0 for Windows. The results of the t-test data analysis carried out showed that there was a significant difference between the control class and the experimental class which was found to have a sig (2-tailed) value of 0.000 0.05.  Therefore, it can be concluded that group guidance with techniques self management effective in reducing academic burnout in class XI MIPA 2 students at MAN 1 LABURA.